Spatial factors play a major role as determinants of endemic ground beetle beta diversity of Madeira Island Laurisilva. - Mário Boieiro (Public Library of Science (PLoS), 2013)
The development in recent years of new beta diversity analytical approaches highlighted valuable information on the different processes structuring ecological communities. A crucial development for the understanding of beta diversity patterns was also its differentiation in two components: species turnover and richness differences. In this study, we evaluate beta diversity patterns of ground beetles from 26 sites in Madeira Island distributed throughout Laurisilva--a relict forest restricted to the Macaronesian archipelagos. We assess how the two components of ground beetle beta diversity (β(repl)--species turnover and β(rich)--species richness differences) relate with differences in climate, geography, landscape composition matrix, woody plant species richness and soil characteristics and the relative importance of the effects of these variables at different spatial scales. We sampled 1025 specimens from 31 species, most of which are endemic to Madeira Island. A spatially explicit analysis was used to evaluate the contribution of pure environmental, pure spatial and environmental spatially structured effects on variation in ground beetle species richness and composition. Variation partitioning showed that 31.9% of species turnover (β(repl)) and 40.7% of species richness variation (β(rich)) could be explained by the environmental and spatial variables. However, different environmental variables controlled the two types of beta diversity: β(repl) was influenced by climate, disturbance and soil organic matter content whilst β(rich) was controlled by altitude and slope. Furthermore, spatial variables, represented through Moran's eigenvector maps, played a significant role in explaining both β(repl) and β(rich), suggesting that both dispersal ability and Madeira Island complex orography are crucial for the understanding of beta diversity patterns in this group of beetles.